Design and Construction of a Non-Invasive Microcontroller Based Blood Sugar Level Measurement Device - Pradita Vistianingsih; Zulfikar Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The design of a non-invasive microcontroller-based blood sugar meter is essential for checking blood sugar levels to ensure blood sugar is always within the normal range for people with diabetes mellitus. This non-invasive blood sugar detector uses a photodiode for reading. This study aims to test and validate the performance of this non-invasive blood sugar meter. The method used is Research and Development (R&D) with the ADDIE development model. Data collection is carried out through the main technique, namely, direct measurement. The trial was carried out through several stages, namely individual testing, small group testing, and field testing. The trial subjects consisted of individuals with a history of diabetes or prediabetes, as well as healthy volunteers who were willing to participate in the study. In this study, the linear regression method was used to analyze the relationship between the results of the device measurements (independent variables) and actual blood sugar levels (dependent variables) obtained through invasive measurements. The results of the study indicate that this tool successfully functions as an alternative to conventional measurement methods, although the accuracy level still requires improvement, with an average accuracy level of 93.45%. The system as a whole has met the functional requirements criteria in terms of the ability to perform measurements, display results via LCD, and transmit data wirelessly. Non-functional requirements such as portability ease have also been met. Comprehensive testing, including black box testing and field trials, proved that system components can function optimally according to the established technical specifications.